Photoelectrons in the quiet polar wind. Issue 6 (14th June 2017) - Glocer, A.; Khazanov, G.; Liemohn, M.
Abstract: This study presents a newly coupled model capable of treating the superthermal electron population in the global polar wind solution. The model combines the hydrodynamic Polar Wind Outflow Model (PWOM) with the kinetic SuperThermal Electron Transport (STET) code. The resulting PWOM‐STET coupled model is described and then used to investigate the role of photoelectrons in the polar wind. We present polar wind results along single stationary field lines under dayside and nightside conditions, as well as the global solution reconstructed from nearly 1000 moving field lines. The model results show significant day‐night asymmetries in the polar wind solution owing to the higher ionization and photoelectron fluxes on the dayside compared to the nightside. Field line motion is found to modify this dependence and create global structure by transporting field lines through different conditions of illumination and through the localized effects of Joule heating. Key Points: Study presents a newly coupled model capable of treating the superthermal electron population in the global polar wind solution Single stationary field line solutions under sunlit and dark conditions are presented as is the global solution from ∼1000 moving lines Field line motion creates global structure by transporting field lines through different conditions of illumination and Joule heating